The Lost Continent - Burroughs, Edgar Rice, 1875-1950 (Salt Lake City, UT : Project Gutenberg, 1994)
"The Lost Continent" by Edgar Rice Burroughs is a novel likely written in the early 20th century. The story is set in a post-apocalyptic future where the Eastern Hemisphere has been cut off from the West for over 200 years following a devastating war. The narrative revolves around Lieutenant Jefferson Turck, a naval officer of the Pan-American Federation, who embarks on a journey beyond the borders set by his civilization, seeking to uncover the mysteries of a long-lost and savage Europe. At the start of the book, Jefferson Turck reflects on the isolation of Europe and the consequences of the Great War that left it abandoned and forgotten. When his ship, the Coldwater, suffers mechanical failures, Turck finds himself crossing the forbidden line into this unknown territory. After a harrowing experience at sea, he and a few crew members wash ashore in a wild and dangerous land. As they navigate this savage world, they encounter exotic beasts and primitive tribes, revealing that civilization has regressed into a state of brutality and ignorance, far removed from the advanced society Turck knows. The opening sets the stage for a gripping adventure filled with peril, exploration, and the struggle to survive amidst the remnants of a once-great civilization. (This is an automatically generated summary.)
Release date is 1994-07-01
Produced by Judith Boss. HTML version by Al Haines.
Keywords: Science fiction; Fantasy fiction; England -- Fiction